PENGARUH MOTIVASI, KOMPETENSI, DAN LINGKUNGAN KERJA TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN COLOMADU KABUPATEN KARANGANYAR - Erni Widajanti, Warsito, Y. Djoko Suseno & (Universitas Slamet Riyadi, 2016)
This study aims to determine the effect of significant motivation, competence, and working environment on public employee performance in the district of Colomadu, Karanganyar. Population of this study were all public employee in the district of Colomadu, Karanganyar consist of 110 people, samples were collected by the census of the number of existing data collection techniques through questionnaires or questionnaire with validity and reliability. Analysis techniques using multiple linear regression with the classical assumption. Conclusion (1) Hypothesis 1 which states â€œMotivation have significant effect on performance on public employee performance in the district of Colomadu, Karanganyarâ€ supported, (2) Hypothesis 2 which states â€œCompetence have significant effect on performance on public employee performance in the district of Colomadu, Karanganyarâ€ supported. (3) Hypothesis 3 which states â€œWork environment have significant effect on performance on public employee performance in the district of Colomadu, Karanganyarâ€ rejected. (4) Hhypothesis 4 which states â€œMotivation is dominant influencing on performance public employee performance in the district of Colomadu, Karanganyarâ€ rejected. Keywords: motivation, competence, work environment, public employee performance